Impact of micro finance on performance of women entrepreneurs in sri lanka evidence from batticaloa district - Jeyan Suganya, D.F.; Yogendrarajah, R. (University of Jaffna, 2018)
Micro finance is considered as major instrument used to protect people from poverty throughout the world. Micro finance institutions in each country are supporting much to women entrepreneurs for achieving their goal by assisting them with providing micro credits, training, saving facilities. The major purpose of this study is to examine the impact of micro finance on performance of women entrepreneurs in Sri Lanka. Credit, savings and training were considered as predictor variables and criterion variable was performance of women entrepreneurs. Standard questionnaire with five point likert scales was used to collect the data from 100 women entrepreneurs functioning in Batticaloa district using stratified sampling method. Descriptive and inferential statistics have been carried out with the use of SPSS package to analyze the data. Cronbach's Alpha was used to ensure the reliability of collected data. It exposed that all the data collected are reliable, since cronbach's Alpha for entire variable was more than 0.6. Coefficient of determination of model revealed that 60% of total variance in performance of women entrepreneur is explained by micro credit, savings and training. The result of this study revealed that training and saving have positive and significant impact on performance of women entrepreneur while micro credit has no significant impact on performance. According to the finding of this study, researcher can conclude that women entrepreneurs can be motivated further by increasing number of training programmes per year since most of women entrepreneurs dropped out of school education and savings to improve performance of their entrepreneur activities. Micro finance institutions can increase loan amount and reduce interest rate to make higher impact on performance of women entrepreneurs. Further result of this study can help to motivate more women in rural areas to engage in entrepreneurial actives for reducing poverty.
Keywords: Microfinance; Microcredit; Savings; Training